Public involvement in chronic respiratory diseases research: A qualitative study of patients', carers' and citizens' perspectives - Margarida Areia; Liliana P. Dias; Paula Matos; Daniela Figueiredo; Ana L. Neves; Emília D. daCosta; Cláudia C. Loureiro; José L. Boechat; António B. Reis; Pedro Simões; Luís Taborda‐Barata; João A. Fonseca; et al. (Wiley, 2024)
Abstract Introduction Patient and public involvement (PPI) initiatives involving patients with chronic respiratory disease (CRD) are rare. Therefore, this study aimed to explore the perspectives of patients with CRD, carers and interested citizens regarding the relevance and need for a PPI network and suggestions for its implementation. Methods A qualitative study based on focus groups was conducted. Recruitment occurred through invitations on social media platforms and to patients who have participated in previous asthma studies of the team. Three focus groups were conducted, via video conference, using a semi‐structured guide. Thematic analysis was performed by two independent researchers and discussed with the extended team. Results Fifteen patients with CRD, one carer and one interested citizen (13 females, median 36 (range: 18-72) years) participated. All participants acknowledged the importance of implementing a collaborative network and demonstrated interest in being integrated. Participants acknowledged the importance of their involvement in several phases of the research cycle. The main aim identified for this network was to facilitate communication between patients and researchers. Participants regarded the integration of patients, carers, researchers and healthcare professionals from different scientific areas as relevant. The use of digital platforms to attract members and support the work, together with group dynamics and regular meetings, were some of the most relevant practical considerations for implementing the network. The identified facilitators for their engagement were sharing experiences, researchers' and healthcare professionals' support and feedback and schedule flexibility. The identified barriers included the amount of time dedicated, low health/digital literacy and the potential detachment of nondiagnosed patients or those with low symptom impact in daily life. Conclusion Patients, carers and citizens acknowledged the relevance of implementing a collaborative network and demonstrated interest in active participation in every stage of the health research cycle. A deeper knowledge of the barriers and facilitators identified in this study could support implementing these initiatives in Portugal. Patient or Public Contribution This study was designed by a research team that included one patient with asthma and one carer. They were specifically involved in building the study protocol and the interview guide. They also gave feedback regarding the electronic consent form and the short sociodemographic questionnaire created, namely by removing noncontributing words or phrases and rewording expressions. The lay summary was written by another patient with asthma. All participants of this study were invited to implement and integrate the ConectAR network-a collaborative network of research in respiratory health. Public Summary In Portugal, chronic respiratory patients do not have an active role as 'coinvestigators'. This study aimed to acknowledge if patients and citizens considered a patient and public involvement network useful, whose main purpose would be to facilitate communication between patients and researchers. A study based on online group interviews was carried out with patients with chronic respiratory diseases and interested citizens, both recruited on social media platforms. Participants considered that bringing together patients, carers, researchers and healthcare professionals is valuable because sharing different experiences and perspectives may help patients to improve their daily lives and increase research quality. In conclusion, patients agree that implementing a collaborative network with researchers and healthcare professionals and participating in the health research cycle is quite preponderant. Acknowledging what can help and deter this network may be beneficial to implementing this type of initiative in Portugal.